THE IMPACT OF SOCIAL MEDIA USE ON LEARNING MOTIVATION AND STUDENT ACHIEVEMENT OF GRADE XII D OF AL AZHAR COLLEGE MEDAN - Keyfun Akbar Kaban; Khairin Hafiz; Khalisah Aprillia Damanik; Rangga Ananda Siregar; Eko Wishnu Wahyudi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Social media has become an important part of adolescents' lives and influences various aspects, including learning motivation and academic achievement. This study aims to analyze the impact of social media use on the learning motivation and academic achievement of class XII D students at Al Azhar Medan's flagship high school. The research method used a quantitative approach with a survey design, involving 28 students as a sample. The research instruments were a social media usage questionnaire, a learning motivation scale, and student academic grade data. The results showed a significant negative relationship between the intensity of social media use and learning motivation, while its effect on academic achievement tended to be moderate. This confirms that excessive social media use has the potential to reduce learning concentration and academic results, although on the other hand, social media can also be used positively as a learning resource. These findings provide important implications for educators, parents, and school policymakers to direct social media use in a more productive direction.